2022
DOI: 10.3389/fmicb.2022.925200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host genetics and gut microbiome on fat deposition traits in pigs

Abstract: Fat deposition affects meat quality, flavor, and production in pigs. Fat deposition is influenced by both genetics and environment. Symbiotic microbe with the host is an important environmental factor to influence fat deposition. In this study, the fat deposition traits were measured in 239 individuals obtained from Tongcheng pigs × Large White pigs resource population. The interactions between genetics and gut microbiome in fat deposition traits were investigated through whole-genome sequencing and cecum micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Metagenome sequencing allows an in-depth investigation of the effects of a single microbiota effect or host-microbiome interaction on the growth, health, and production performance of the host [127][128][129], which has great potential to dissect complex animal traits. To date, only two studies related to porcine fat deposition and feed conversion traits have been reported [115,130]. MWAS reveals that Anaeroplasma, Paraprevotella, Pasteurella, and Streptococcus abundances were significantly associated with the percentage of leaf fat, and Sharpea and Helicobacter abundance exhibited significant associations with intramuscular fat [130].…”
Section: Metagenome-wide Association Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenome sequencing allows an in-depth investigation of the effects of a single microbiota effect or host-microbiome interaction on the growth, health, and production performance of the host [127][128][129], which has great potential to dissect complex animal traits. To date, only two studies related to porcine fat deposition and feed conversion traits have been reported [115,130]. MWAS reveals that Anaeroplasma, Paraprevotella, Pasteurella, and Streptococcus abundances were significantly associated with the percentage of leaf fat, and Sharpea and Helicobacter abundance exhibited significant associations with intramuscular fat [130].…”
Section: Metagenome-wide Association Studiesmentioning
confidence: 99%
“…To date, only two studies related to porcine fat deposition and feed conversion traits have been reported [115,130]. MWAS reveals that Anaeroplasma, Paraprevotella, Pasteurella, and Streptococcus abundances were significantly associated with the percentage of leaf fat, and Sharpea and Helicobacter abundance exhibited significant associations with intramuscular fat [130]. However, only a limited number of operational taxonomic units has been found to be associated with residual feed intake (RFI), feed conversion ratio, daily feed intake, and back fat thickness [115].…”
Section: Metagenome-wide Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the joint contribution of the host genome and the gut microbiome to complex traits has recently received much attention. For example, several studies have demonstrated the potential value of the microbiome in predicting obesity in humans (Rothschild et al., 2018 ), fat deposition and feed efficiency in chickens (Wen et al., 2019 , 2021 ), milk fatty acid composition in dairy cows (Buitenhuis et al., 2019 ; Zang et al., 2022 ), and fat deposition and performance traits in pigs (Aliakbari et al., 2022 ; Wang, Zhou, et al., 2022 ). Moreover, combining gut microbiome and host genome data could significantly improve the prediction accuracy for complex traits (Perez‐Enciso et al., 2021 ; Rothschild et al., 2018 ).…”
Section: Variance Partitioning Analyses Have Revealed That Meat Quali...mentioning
confidence: 99%
“…Interestingly, the amplicon sequence variant of several genera (including Vibrio anaerobic , Bacillus mimicus , Bacillus cereus , Bacillus faecalis , and Lactobacillus ) is significantly correlated with feed efficiency, and this effect exists at different growth stages in monogastric animals [ 13 ]. Microbes regulate numerous biological functions of the host [ 14 ], and numerous studies have shown that microbes regulate fat deposition in animals [ 15 , 16 ]. Thus, animals with different phenotypes may have their specific microbiota characteristics in the gastrointestinal tract at the genetic level.…”
Section: Introductionmentioning
confidence: 99%